PENGARUH DISIPLIN KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU DIMODERASI LINGKUNGAN KERJA Di MTs SEKECAMATAN WINONG KABUPATEN PATI - Asyhar, 12.5202.0258; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aimed to examine the effect of labor discipline and competence ofteachers on teacher performance in MTs Sekecamatan Winong moderated Pati regencywith the work environment. The specific objectives of this study was to examine the effectof labor discipline and competence of teachers on teacher performance are moderated bythe role of the working environment. The usefulness of this study is to clarify and extendprevious research on the effect of labor discipline and competence of teachers on teacherperformance are moderated working environment.This study used a population of teachers in MTs Sekecamatan Winong Patiregency much as 173 teachers. Sampling techniques in this research is proportional to thepurposive sampling method.Based on the results of the study can be summarized as follows labor disciplineeffect on the performance of teachers, teacher competence has no effect on theperformance of the teacher, the work environment affect the performance of teachers,working environment weaken labor discipline relation to the performance, and the workenvironment does not affect the relationship of teacher competence on performance.Keywords: work discipline, teacher competence, work environment, the performance of teachers.